INTERAKSI GENETIK X LINGKUNGAN DAN STABILITAS JUMLAH BUAH 11 AKSESI PINANG LOKAL DENGAN PENDEKATAN PARAMETRIK - Muhammad Roiyan Romadhon; Meity Aneke Tulalo (JURNAL AGRONIDA, 2020)
Areca is an annual plant that has many benefits and a high economy. The need for areca nuts for industry is a challenge because only two varieties have been released and little farmers who plant areca nuts. Exploration of superior areca candidates are one way to overcome this problem. This aim of research is to determine the stability and adaptability of 12 local areca nuts to the number of fruit. This research was conducted at Kayuwatu Expermental Farm for 4 years from 2014-2017. The experimental design used was Randomized Complete Block Design (RCBD) 2 replications with 15 sample plants. The result of the research showed that Malinow 2 accession is a stable accession based on the stability analysis of Finlay Wilkinson and Eberhart Russel and can grow in a marginal environment, while Huntu 1 and Galangsuka Accession is a stable accession in optimal environment.